Dental rehabilitation in complex treatment of patients with neoplasms of the maxillofacial region - E. V. Kochurova; V. N. Nikolenko; P. A. Demenchuk; A. S. Utjuzh; M. V. Loktionova; S. V. Tereshhuk; I. L. Hvatov; E. O. Kudasova (Кубанский научный медицинский вестник, 2015)
Tumors of the maxillofacial region are complicated by the problem of prosthetic dentistry. The complexity of the location, diversity, localization, fast growth, high morbidity and risk of progression and recurrence are the reason for late diagnosis and volumetric destructive interventions. In this regard, all the more there is a need for non-invasive diagnosis in the dental admission for additional early diagnosis, monitoring and determination of the effect of treatment of this category of patients.